Editorial: Using the D-dimer test in infective endocarditis - Recep Demirbağ (KARE Publishing, 2013)
D-dimer is a global indicator of coagulation activation. Levels of D-dimer are elevated in a wide variety of inflammatory and prothrombotic conditions. Clinicians should be aware of the possibility of systemic embolism in infective endocarditis patients with elevated D-dimer levels. Comprehensive evaluation of the patients, consisting of clinical risk assessment in combination with measurement of D-dimer level besides other suggested risk parameters for embolism in infective endocarditis.